TRANSFORMASI HAND TRAKTOR BEKAS MENJADI TRAKTOR PERAHU UNTUK PERTANIAN PADA GAPOKTAN DESA KERTABUANA KABUPATEN KUTAI KARTANEGARA - FX. Arif Wahyudianto; Anni Fatmawati; wajilan; surianto; Mimin Rihotimawati; Simon Petrus; Merpatih (P3M Politeknik Negeri Malang, 2026)
This community service program aims to address the critical challenges of mechanization in Kertabuana Village, Kutai Kartanegara, whose land is dominated by deep peat swamps and degraded due to mining expansion, turning the rice center into a difficult to cultivate area. The significance of the program lies in the provision of adaptive technology solutions for Gapoktan, which enables sustainable land cultivation, improves operational efficiency, and supports the village's commitment to the development of agricultural infrastructure such as reservoirs and irrigation. Implementation was carried out through the transformation of used hand tractors into boat tractors with special flotation systems and wetland propulsion, followed by intensive technical training for Gapoktan members, which included operations, engine maintenance (including components such as clutches and fuel valves).The results of the program show the success of the Boat Tractor in penetrating deep layers of mud, where conventional tools fail, significantly reducing the need for intensive manual labor, saving time and operational costs, and ensuring that planting schedules can be met in a timely manner, thereby strengthening the economic resilience of farmers and supporting the restoration of village agricultural identity.